Endoplasmic reticulum–endosome contact increases as endosomes traffic and mature - Friedman, Jonathan R. (The American Society for Cell Biology, 2013)
The endosomal pathway is responsible for plasma membrane cargo uptake, sorting, and, in many cases, lysosome targeting. Endosome maturation is complex, requiring proper spatiotemporal recruitment of factors that regulate the size, maturity, and positioning of endosomal compartments. In animal cells, it also requires trafficking of endosomes on microtubules. Recent work has revealed the presence of contact sites between some endosomes and the endoplasmic reticulum (ER). Although these contact sites are believed to have multiple functions, the frequency, dynamics, and physical attributes of these contacts are poorly understood. Here we use high-resolution three-dimensional electron microscopy to reveal that ER tubules wrap around endosomes and find that both organelles contact microtubules at or near membrane contact sites. As endosomes traffic, they remain bound to the ER, which causes the tubular ER to rearrange its structure around dynamic endosomes at contact sites. Finally, as endosomes transition through steps of maturation, they become more tightly associated with the ER. The major implication of these results is that endosomes mature and traffic while coupled to the ER membrane rather than in isolation.